Effectiveness of trans-scleral cyclophotocoagulation for refractory paediatric glaucoma (Journal of Fatima Jinnah Medical University, 2022)
Background: The aim of this study was to find out the effectiveness of trans-scleral cyclophotocoagulation in lowering intraocular pressure in the paediatric population.Patients and methods: This quasi-experimental study was conducted between July 2020 and January 2021 in Department of Ophthalmology, The Children’s Hospital, Lahore. Total 45 eyes of 42 children of age 1-14 years, both genders, with glaucoma were enrolled in this study. Diode cyclophotocoagulation unit and probe of make Quantel Medical was used for cycloablation under general anesthesia. Postoperative intraocular pressure was noted by using handheld Perkins applanation tonometer Mk2 after every 3 weeks for 12 weeks. If an IOP of ≤21mmHg was achieved, then efficacy or success was labeled. Patients with an IOP of >21mmHg after 12 weeks were selected for repeat cycloablation treatment. Failure was labeled to an IOP of >21mmHg even after a repeat session. Data analysis was done using SPSS 24. Results: In this study, 45 eyes were included with a mean age of 4.49 ± 3.12 years. There were 21 (46.7%) males and 24 (53.3%) females. At the time of presentation, the most common diagnosis was primary congenital glaucoma [28 (62.2%)], followed by aphakic glaucoma [10 (22%)], Anterior segment dysgenesis [2 (4.4%)], Pseudophakic glaucoma [2 (4.4%)], Sturge weber syndrome [2 (4.4%)] and Post-traumatic [1 (2.2%)]. The mean IOP at baseline was 26.67±3.66 mmHg, which was reduced to 19.60±6.33 mmHg with mean change in IOP of 7.07±4.56 mmHg (p
Keywords: Diode cyclophotocoagulation; Paediatric glaucoma; Intraocular pressure; Refractory